DETERMINATION OF NURSING STUDENTS' PERCEPTION OF ACCREDITATION - KOÇOĞLU, Ferdane (Göbeklitepe Medical Science Journal, 2024)
This study was conducted to determine the perceptions of nursing students towards accreditation. The population of the descriptive study consisted of a total of 450 students studying in the department of nursing. The study was completed with the participation of 348 students. The research was conducted online using Google form. Socio-demographic information form and "Accreditation Perception Scale" were used to obtain the data. The data were evaluated using descriptive statistics. 70.4% of the students who participated in the research see the accreditation activities carried out as necessary. 82.2% of the students stated that accreditation activities have a positive effect on the quality of the university and 81.9% of them have a positive effect on branding. The majority of the students who participated in the research stated that accredited universities are different from the universities where they study and that this difference is due to the organization/participation of social activities and the evaluation of students. The overall mean of the "Perception of Accreditation Scale" of the students participating in the study was 3.31, while it was 3.26 for Quality Assurance and 3.34 for Quality Assessment. It was determined that the mean score for Quality Assurance was lower than the mean score for Quality Assessment. It was determined that students' perceptions of accreditation were at a moderate level according to the Accreditation Perception Scale. In order to further increase students' perceptions of accreditation, which are at a moderate level, it may be recommended to organize training programs that ensure their active participation at every stage of the accreditation process.